Effects of depression on patients suffering from ankylosing spondylitis: a comparative study. - Cortés-Rodríguez, Antonio; Alves-Gomes, Lisa; Losa-Iglesias, Marta Elena; Gómez-Salgado, Juan; Becerro-de-Bengoa-Vallejo, Ricardo; Saavedra‐García, Miguel Ángel; López-López, Daniel; Jiménez-Cebrián, Ana María (Associação Paulista de Medicina, 2025)
BACKGROUND: Ankylosing spondylitis (AS) is a sustained inflammatory pathology that manifests as increasing rigidity and a continuous decline in spinal flexibility, leading to increasing lumbar pain during rest. OBJECTIVES: This study primarily aimed to evaluate depression assessments using the Beck Depression Inventory (BDI) and delineate depressive symptomatology in patients diagnosed with AS compared to those without this condition. DESIGN AND SETTING: A comparative study was conducted in Medical Centers in Málaga, Spain. METHODS: A cohort of 102 participants, with a mean age of 46,80 ± 10,54 years, was divided into two sets: 51 individuals diagnosed with AS (cases) and another 51 without AS (controls), each harmonized across variables such as body mass index, age, and sex. Demographic variables were systematically gathered from each participant, and the BDI responses were accurately recorded and subsequently analyzed for comparison. RESULTS: Of the total sample, the sex distribution was 29.4% male and 70.6% female. BDI scores were higher for the AS group (19.25 ± 15.5) than for the control group (5.33 ± 7). Notably, there were clear statistical differences (P < 0.01) in the BDI categories, with elevated levels observed in participants with AS. CONCLUSIONS: Individuals with AS experienced higher levels of depression than those without AS. Furthermore, there were sex differences within the case group, with a higher percentage of women than men at any level of depression. Notably, there was a moderate inverse correlation between the number of years since diagnosis and depression level.
Keywords: Espondiloartropatías; Pie - Anomalías y malformaciones; Beck depression inventory; Psychological assessment; Chronic inflammatory diseases